Evolution of radiographic joint damage in rituximab-treated versus TNF-treated rheumatoid arthritis cases with inadequate response to TNF antagonists. Issue 10 (14th March 2012) - Finckh, Axel; Möller, Burkhard; Dudler, Jean; Walker, Ulrich A; Kyburz, Diego; Gabay, Cem
Abstract : Background: Observational studies have suggested that patients with rheumatoid arthritis (RA) who experience inadequate response to anti-tumour necrosis factor (anti-TNF) agents respond more favourably to rituximab (RTX) than to an alternative anti-TNF agent. However, the relative effectiveness of these agents on long-term outcomes, particularly in radiographic damage, remains unclear. Objective: To compare the effectiveness of RTX against anti-TNF agents in preventing joint damage in patients with RA who have experienced inadequate response to at least one prior anti-TNF agent. Methods: This is a prospective cohort study within the Swiss registry of patients with RA who discontinued at least one anti-TNF agent and subsequently received either RTX or an alternative anti-TNF agent. The primary outcome, progression of radiographic joint erosions (Ratingen erosion score)over time, and the secondary outcome, functional disability (Health Assessment Questionnaire Disability Index), were analysed using regression models for longitudinal data and adjusted for potential confounders. Results: Of the 371 patients included, 104 received RTX and 267 received an alternative anti-TNF agent. During the 2.6-year median follow-up period, the rates of Ratingen erosion score progression were similar between patients taking RTX and patients taking an alternative anti-TNF agent (p=0.67). The evolution of the Health Assessment Questionnaire score was statistically significantly better in the RTX group (p=0.016), but the magnitude of the effect was probably not clinically relevant. Conclusion: This observational study suggests that RTX is as effective as an alternative anti-TNF agent in preventing erosions in patients with RA who have previously experienced inadequate response to anti-TNF agents.